2008
DOI: 10.1093/ejechocard/jen317
|View full text |Cite
|
Sign up to set email alerts
|

Contrast echocardiography for pulmonary arteriovenous malformations screening: does any bubble matter?

Abstract: CE is an extremely sensitive procedure for the detection of PAVMs with substantial clinical impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 22 publications
8
68
1
3
Order By: Relevance
“…In one series, positive contrast echocardiography reflecting intrapulmonary shunting was found in 85% of HHT1 patients, and 35% of HHT2 patients 52 compared to 7% of a control normal population. 47 Patients with HHT2 have a higher prevalence of hepatic AVMs, 23,[25][26][27] and of severe disease due to hepatic AVMs 27,70 . A single series suggests HHT2 patients may have more pancreatic AVMs 9 , and develop dermal telangiectasia earlier than in HHT1.…”
Section: 2b) Genotype Phenotype Correlationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one series, positive contrast echocardiography reflecting intrapulmonary shunting was found in 85% of HHT1 patients, and 35% of HHT2 patients 52 compared to 7% of a control normal population. 47 Patients with HHT2 have a higher prevalence of hepatic AVMs, 23,[25][26][27] and of severe disease due to hepatic AVMs 27,70 . A single series suggests HHT2 patients may have more pancreatic AVMs 9 , and develop dermal telangiectasia earlier than in HHT1.…”
Section: 2b) Genotype Phenotype Correlationsmentioning
confidence: 99%
“…Long term follow up: Post embolisation CT at 6-12 months then 3 yearly; small untreated, or CE positive, 1-5 yearly. [47][48][49][50][51] , and frequency of positive results 52 . New natural history data re stroke/brain abscess (risks independent of PAVMs size imply need to treat all PAVMs feasible 34 ; migraines 53,54 ; pregnancy rupture 55 .…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary and cerebral AVMs can cause complications, such as intracranial bleeding, brain abscess, ischaemic stroke and pulmonary haemorrhage, and screening of at-risk populations has been advocated [23][24][25][26][27][28][29][30][31][32]. Studies in adult patients have demonstrated that significant pulmonary and cerebral AVMs can be detected in asymptomatic patients [5,6,22,[31][32][33][34][35][36][37][38][39], and that preventative treatment can reduce the rate of complications [32]. This is less well established in children, and recent studies have suggested that the overall rate of complications is low in this age group [23,32].…”
mentioning
confidence: 99%
“…Among screening modalities, TTCE appears to be the single most sensitive screening test for PAVMs [5] . TTCE alone [8] or in combination with plain chest radiography [5] has been reported to be 100% sensitive for, and able to definitively rule out, PAVMs in patients with shunts. At least some authors have argued, however, that addition of plain chest radiography to TTCE exposes patients to ionizing radiation without demonstrated improvement in detection of PAVMs [9] .…”
Section: Discussionmentioning
confidence: 99%